THE INFLUENCE OF ORGANIZATIONAL COMMITMENT, JOB RISK AND WAGE LEVELS ON JOB SATISFACTION PT EMPLOYEES NINJA EXPRESS BRANCH TEBING TINGGI CITY - Rodi Syafrizal (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
The purpose of this research is to determine the influence of organizational commitment, work risk and wage levels on job satisfaction of PT employees. Ninja Express Tebing Tinggi City branch. The population in this study were all employees of PT. Ninja Express branch of Tebing Tinggi City works as a courier with 44 respondents. The data source in this research comes from primary data, namely from the results of collecting questionnaires filled in directly by respondents. Hypothesis testing uses multiple regression analysis on the SPSS version 25 application. The results of this study show that partially organizational commitment and work risk do not have a significant effect on employee job satisfaction at PT. Ninja Express Tebing Tinggi City Branch. Meanwhile, the wage level influences the job satisfaction of PT employees. Ninja Express Tebing Tinggi City Branch. Simultaneously or together, organizational commitment, work risk and wage levels influence PT employee job satisfaction. Ninja Express Tebing Tinggi City Branch.